1999
DOI: 10.1080/10473289.1999.10463824
|View full text |Cite
|
Sign up to set email alerts
|

Bioaerosol Concentration at an Outdoor Composting Center

Abstract: Compost centers are one of many environments that produce airborne microorganisms. The objective of this study was to compare the bacterial, fungal, and actinomycete concentrations at the Norman, OK, compost center to background concentration of these same microorganisms. For this comparison, a modified Andersen Microbial Sampler was used. Sampling was performed at three sites at the outdoor compost center and at two background sites. The concentration of each microorganism was measured as total colony forming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 12 publications
(12 reference statements)
1
25
0
1
Order By: Relevance
“…The average concentration of bacteria determined in this study was comparable with data reported for bacterial concentrations at composting facilities in a number of previous studies (Folmsbee and Strevett 1999;Hryhorczuk et al 2001;Sanchez-Monedero et al 2005), and lower than that found in others (Swan et al 2003;Taha et al 2006). In comparison, bacterial levels were found to be higher than those of fungal aerosols.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The average concentration of bacteria determined in this study was comparable with data reported for bacterial concentrations at composting facilities in a number of previous studies (Folmsbee and Strevett 1999;Hryhorczuk et al 2001;Sanchez-Monedero et al 2005), and lower than that found in others (Swan et al 2003;Taha et al 2006). In comparison, bacterial levels were found to be higher than those of fungal aerosols.…”
Section: Discussionsupporting
confidence: 91%
“…Previous investigations have largely studied bioaerosol from composting plants or facilities (Van der Werf 1996;Folmsbee and Strevett 1999;Hryhorczuk et al 2001;Sanchez-Monedero et al 2005;Taha et al 2006). A few studies have looked at bioaerosol release from land application of biosolids and potential hazards posed by this (Pillai et al 1996;Gerba et al 2002;Brooks et al 2004;Brooks et al 2005); however, it seem that data relating to bioaerosol emissions as a result of application of municipal solid waste (MSW) compost are lacking.…”
Section: Introductionmentioning
confidence: 96%
“…These results were in the range 10 3 -10 6 cfu m Ϫ3 , which is in agreement with the results of other authors working with similar conditions. 6,[9][10][11][12] The amounts recorded at downwind locations D2, D3, and D5 (200 and 300 m downwind) during vigorous activity were similar to background levels, reflecting the good air dispersion (Figure 2). The airborne concentrations at these downwind locations were occasionally slightly above the background levels, but never exceeded 2.9 ϫ 10 3 cfu m Ϫ3 .…”
Section: ϫ3mentioning
confidence: 99%
“…Aerosolized microbes may originate from agricultural fields 2 , sewage treatment centres 3 , geothermal springs 4 , any surface exposed to sufficient wind force 5 and large-scale volcanic eruptions 6 . Organisms that have been independently aerosolized or attached to dust particles can be transported thousands of kilometres, which presumably allows microbes to easily move between continents and hemispheres [7][8][9][10][11] .…”
mentioning
confidence: 99%